The restorative effects of nature: Experimental methodologies from Environmental Psychology and opportunities for Architecture - López Valverde, Derek (2021)
Environmental psychology is a branch that studies the exchanges between humans and their physical environments. Over the past several years, a significant amount of international investigations haverecognized the benefits that natural environments, and their characteristics, produce in human beings. Thispaper carries out a bibliographic review about the principal experimental methodologies that have beenused from environmental psychology, which including simulations conducted in laboratory (images, videosand virtual reality), and field experiments (walking and landscape contemplation). Throughout the review,the benefits that natural environments, both physical and simulated, cause in human being and thepossibilities it provides for their use are analyzed. Finally, the main generalities in the methodologies, thebenefits of nature within the urban and the need to increase interdisciplinary research are discussed.